A piece of the world (Colorado State Library Book Club Collection): a novel (William Morrow, an imprint of HarperCollinsPublishers, 2017)
To Christina Olson, the entire world was her family's remote farm in the small coastal town of Cushing, Maine. Born in the home her family had lived in for generations, and increasingly incapacitated by illness, Christina seemed destined for a small life. Instead, for more than twenty years, she was host and inspiration for the artist Andrew Wyeth, and became the subject of one of the best known American paintings of the twentieth century.

Orphan train (Colorado State Library Book Club Collection): a novel (William Morrow, 2012)
"Penobscot Indian Molly Ayer is close to 'aging out' out of the foster care system. A community service position helping an elderly woman clean out her home is the only thing keeping Molly out of juvie and worse.... As she helps Vivian sort through her possessions and memories, Molly learns that she and Vivian aren't as different as they seem to be. A young Irish immigrant orphaned in New York City, Vivian was put on a train to the Midwest with hundreds of other children whose destinies would be determined by luck and chance. Molly discovers that she has the power to help Vivian find answers to mysteries that have haunted her for her entire life--answers that will ultimately free them both. Rich in detail and epic in scope, Orphan Train by Christina Baker Kline is a powerful novel of upheaval and resilience, of unexpected friendship, and of the secrets we carry that keep us from finding out who we are"--from publisher's description.
Penobscot Indian Molly Ayer is close to 'aging out' out of the foster care system. A community service position helping an elderly woman clean out her home is the only thing keeping Molly out of juvie and worse ... As she helps Vivian sort through her possessions and memories, Molly learns that she and Vivian aren't as different as they seem to be. A young Irish immigrant orphaned in New York City, Vivian was put on a train to the Midwest with hundreds of other children whose destinies would be determined by luck and chance. Molly discovers that she has the power to help Vivian find answers to mysteries that have haunted her for her entire life , answers that will ultimately free them both. Rich in detail and epic in scope, Orphan Train by Christina Baker Kline is a powerful novel of upheaval and resilience, of unexpected friendship, and of the secrets we carry that keep us from finding out who we are.